Body piercing and tattoo: awareness of health related risks among 4,277 Italian secondary school adolescents - Mazzoleni Francesco; Benetton Mirca; Bortolotto Melania; Miatto Enrico; Cegolon Luca; Mastrangelo Giuseppe (BMC, 2010)
Abstract Background The awareness of health risks associated with body art among secondary school pupils has never previously been studied in depth. A large sample of secondary school adolescents from the Veneto Region (North East Italy) were investigated in order to inform health education programs. Methods 6 public secondary schools from each of the 7 Provinces of the Veneto Region were selected. All students attending the 1st, 3rd, and 5th school years were surveyed by an anonymous self administered questionnaire on their perception of health risks related to body art and other explanatory variables. Logistic regression analysis was employed, reporting adjusted Odds Ratios (OR) with 95% Confidence Interval (CI). Results Among 4,277 available students (aged 14-22 years), boys were consistently: less knowledgeable of infectious diseases related to body art (OR = 0.78; CI: 0.66, 0.94), less likely to be aware of the hygienic norms to be observed in a body art parlour (OR = 0.54; 0.44, 0.65), less likely to refer to a certified body art parlour (OR = 0.56; 0.48, 0.66), less likely to refer to a professional health care provider for complications related to body art (OR = 0.71; 0.59, 0.86). Students attending the first school year (baseline) had a lesser knowledge of body art related infectious diseases, were less likely to refer to a certified body art parlour, and to know the mandatory hygienic rules to be observed when performing body modifications. Interviewees from the provinces of Rovigo and Vicenza were less likely to be conscious of the health risks associated with body modifications, and those with tattoos were less knowledgeable about the infection risk (OR = 0.60; 0.42, 0.86) and less likely to refer to a professional health care provider in case of medical complication (OR = 0.68;0.48, 0.95). Students with piercings were less likely to refer to a certified practitioner for receiving body art (OR = 0.62; 0.50, 0.77) or therapy for medical complications (OR = 0.37; 0.29, 0.46). Conclusions Health education programs should focus on males, pupils attending lower school years, living in specific Provinces of the Region, and with a positive attitude towards piercing or tattoo.